APPORT A L’ETUDE DES RISQUES DE L’INFRASTRUCTURE FERROVIAIRE, QUELLES IMPLICATIONS SUR LA DISTRIBUTION PHYSIQUE DES VEHICULES DU SITE DE PRODUCTION AUTOMOBILE DE MELLOUSA (TANGER - MAROC)? - JAMÏ, Jihad; AMRANIA, Hajar (European Scientific Journal, ESJ, 2014)
The logistics optimization issues are at the heart of the concerns of industrial enterprises. Indeed, a better management of the supply chain lies in the control of constraints QCT (quality-cost-time), the three pillars of performance. In this context, the choice of solutions for physical distribution of products is of capital importance, since they determine the optimization goal. The choice is even more compelling, with the current trend towards green logistics. In this regard, "Renault Tanger Exploitation", freshly implanted in northern Morocco, with 94% of production for export, directs the management of downstream logistics processes to more fluidity thanks to the use of the railroad. Therefore, several questions arise around security approach – transport of vehicles. Does the railroad provide operational continuity of logistics flows? What are the current and potential risks that can be identified? ... The objective being to reduce the risk of stopping the rail flow which has a direct impact on the ability of the storage of manufactured vehicles and the production flow.